INNOVATIVE DEVELOPMENT OF ORGANIZATIONAL AND ECONOMIC MECHANISMS OF ECONOMIC GROWTH IN THE SERVICE SECTOR OF THE REPUBLIC OF UZBEKISTAN (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The organization of the organizational and economic mechanism that has been formed in the service sector in our republic for full control and management of the services market. Classification of indicators that determine economic efficiency in the service sector, and the study of the methodology for assessing labor efficiency.